Merger dan Acquisition in Vietnam: Impact on Wealth, Quality of Governance, and Policy Implications in Emerging Markets - Kenanya, Zerahya; Ramadhaning, Dea Nur; Baihaqqi, M. Faizal; Farizi, M. Harit; Nurdin , Omair Davy Zakaria; Suryaningrum, Diah Hari (PT Global Digital Sains Tekno, 2025)
Purpose: To understand the impact of mergers and acquisitions (M&A) in Vietnam, with particular emphasis on the differences between the intended and acquired companies, this study also considers institutional, regulatory, and macroeconomic variables that may influence the results. Method: The study analyzed twenty relevant articles published between 2015 and 2025. The method used was a descriptive-analytical literature review. To identify the elements, differences, and variables influencing the wealth effects of M&A in Vietnam, these articles were assessed comparatively and thematically. Findings: This study shows that as a result of the acquisition premium, target shareholders often experience unusually positive returns; conversely, acquirer shareholders often experience neutral or negative returns, supporting agency theory. Foreign investors, information asymmetry, regulatory uncertainty, and transaction aspects such as deal size and cross-border nature are some examples of moderating factors. Implication: These results suggest that improving M&A outcomes in emerging markets requires improved corporate governance, greater regulatory clarity, and market transparency. While practitioners recommend that policymakers prioritize macroeconomic stabilization and enhancing investor protection mechanisms, post-merger integration and in-depth due diligence should be a top priority. Originality:These results suggest that to improve M&A outcomes in emerging markets, better corporate governance, greater regulatory clarity, and market transparency are necessary. Keywords: Mergers and Acquisitions, Corporate Management, Wealth Effect, Emerging Markets.